PENEGAKAN HUKUM TINDAK PIDANA PUNGUTAN LIAR YANG DILAKUKAN DESA ADAT DITINJAU DARI PERSPEKTIF HUKUM PROGRESIF - Ni Luh Sri Mahendra Dewi (Fakultas Hukum Universitas Dwijendra, 2020)
Since the issuance of Presidential Regulation No. 87 of 2016 concerning the Clean Sweep Task Force (Satgas Saber Pungli), several times law enforcement officers have arrested the officers of the Adat Village who have levied in their territories. These levies are carried out based on the awig-awig and/perarem applicable in the Customary Village, but in the perspective of the Pungli Saber Task Force, these levies are qualified as criminal acts of illegal levies. The law enforcement action creates unrest and raises polemics within the community, so it is important to be investigated. This study aims to identify and analyze two problems, namely (1) regarding the efforts made by law enforcers on acts of illegal fees carried out by Adat Village; and (2) the need for progressive law enforcement against illegal acts of crime committed by Desa Adat. The above problems were examined using normative legal research methods, with a legal approach and conceptual approach. The materials used in this study include legal materials (primary legal materials and secondary legal materials) and non-legal materials, which are collected through literature search techniques in libraries and the internet. The materials that have been found are then read and recorded. After the relevant research materials are collected, they are then processed and analyzed by reasoning techniques and legal arguments, such as legal construction techniques and legal interpretation. The overall results and discussion of this study are presented descriptively. The results of the study show the following conclusions. First, the legal efforts taken by law enforcers against illegal acts of crime committed by Desa Adat are to enforce procedural law with an orientation that emphasizes the provision that anyone who levies outside the statutory provisions qualifies as illegal levies, so that it must be processed law. Second, law enforcers need to implement progressive law enforcement in dealing with illegal acts of crime committed by Desa Adat in order to provide substantive justice to the Desa Adat who carry out levies based on the adat village perarem. Keywords: Customary Village, Illegal Levies, Progressive Law Enforcement.